Truncus bicaroticus with aberrant origin of right subclavian artery in a patient with atrioventricular septal defect: A rare aortic branch anomaly - Apurva A. Javalgi; Resham Singh; Civilee Nanda; Rohini Gupta Ghasi (Annals of Pediatric Cardiology)
Aortic arch branching anomalies are rare incidental findings in angiographies performed for cardiovascular and cerebrovascular causes. Recognizing them and candid reporting are crucial for treatment planning, interventional access sites for catheterization, catheter selection, and deciding the need for further imaging. We report a rare case of truncus bicaroticus with the aberrant origin of the right subclavian artery in a patient with an atrioventricular septal defect diagnosed on computerized tomography angiography and highlight its clinical implications.